2011
DOI: 10.1253/circj.cj-10-0552
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Smoking on Arterial Stiffness

Abstract: Background:The brachial-ankle pulse wave velocity (baPWV) and cardio-ankle vascular index (CAVI) are used to evaluate arterial distensibility. The purpose of this study was to elucidate the acute and chronic effects of smoking on arterial stiffness as measured by baPWV and CAVI. Methods and Results:Ten male smokers were studied to evaluate the acute effect of smoking on arterial stiffness. To elucidate the chronic effect of smoking on arterial stiffness, 160 male active smokers were analyzed. CAVI and baPWV we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 29 publications
5
58
3
1
Order By: Relevance
“…Smoking has been found to be a risk factor for increasing arterial stiffness 17) . One study noted that smoking causes a significant increase in arterial stiffness as measured by the CAVI and that the CAVI correlates with the Brinkman index, which suggests that the CAVI is a useful index of the degree of arterial stiffness caused by smoking 18) . Another study found that complete smoking cessation improves the CAVI value 19) .…”
Section: Resultsmentioning
confidence: 99%
“…Smoking has been found to be a risk factor for increasing arterial stiffness 17) . One study noted that smoking causes a significant increase in arterial stiffness as measured by the CAVI and that the CAVI correlates with the Brinkman index, which suggests that the CAVI is a useful index of the degree of arterial stiffness caused by smoking 18) . Another study found that complete smoking cessation improves the CAVI value 19) .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, since we instructed smokers to abstain from cigarette smoking for 3 hours prior to reporting to the laboratory, the potential for NO 3 -supplementation to offset the transient increase in blood pressure [80] and lowering of plasma [NO 2 -] [58] was not explored in this study and could represent a positive effect of dietary NO 3 -supplementation in cigarette smokers. It is also important to stress that, although the findings of this study suggest that cigarette smokers might not improve blood pressure if they increase dietary NO 3 -intake, increased NO 3 --rich vegetable consumption will provide other nutrients that can benefit human health [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…9 Acute exposure to cigarette smoking may be associated with inflammation, thrombosis, endothelial dysfunction, arterial stiffness, and coronary microvascular dysfunction. [10][11][12][13][14][15][16][17] Cohort studies have traditionally been used to examine the chronic effects of smoking, but have rarely been used to evaluate immediate inhalational smoking exposure. 18 Long-term exposure is commonly assessed using smoking duration (years), or cumulative exposure (pack-years).…”
Section: Introductionmentioning
confidence: 99%